2018
DOI: 10.1002/gamm.201740005
|View full text |Cite
|
Sign up to set email alerts
|

On the Non‐Polyhedricity of Sets with Upper and Lower Bounds in Dual Spaces

Abstract: We demonstrate that the set L∞(X, [−1,1]) of all measurable functions over a Borel measure space (X, B, μ) with values in the unit interval is typically non‐polyhedric when interpreted as a subset of a dual space. Our findings contrast the classical result that subsets of Dirichlet spaces with pointwise upper and lower bounds are polyhedric. In particular, additional structural assumptions are unavoidable when the concept of polyhedricity is used to study the differentiability properties of solution maps to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…is in general not polyhedric, as the counterexamples in [5,6,28] demonstrate. If one assumes that this set is polyhedric, then the analysis of [12,19] can be adapted to prove the directional differentiability of S, see [17,23].…”
Section: The Lasso Problem In Sobolev Spacesmentioning
confidence: 99%
“…is in general not polyhedric, as the counterexamples in [5,6,28] demonstrate. If one assumes that this set is polyhedric, then the analysis of [12,19] can be adapted to prove the directional differentiability of S, see [17,23].…”
Section: The Lasso Problem In Sobolev Spacesmentioning
confidence: 99%
“…(Ω)} is not polyhedric in H −1 (Ω) (see the recent contribution [9]). Thus, additional assumptions have to be imposed in [11] to guarantee the polyhedricity.…”
Section: Directional Differentiabilitymentioning
confidence: 99%
“…The idea is to make use of the polyhedricity of the test set ∂ϕ(0) appearing in the dual formulation of the constraint in (P b ). By means of [9,Thm. 2.3], this property allows us to derive the directional differentiability of the solution operator, which leads to a strong stationary optimality system.…”
mentioning
confidence: 99%
“…An alternative polyhedricity hypothesis has been considered recently in [43]. Although the latter apparently avoids structural assumptions on the active set, in the recent work [19] it is shown that in order to get polyhedricity, structural assumptions on the active set are actually unavoidable. Theorem 3.6 Let f, h ∈ L r (Ω) with r > max{d/2, 1} be given.…”
Section: )mentioning
confidence: 99%